Rediseño del Centro Comercial Mercado Sur de la ciudad de Ambato - Escobar López, Francisco Marcelo (2024)
The present integrative work is developed with the aim of proposing a comprehensive redesign for the Mercado Sur Shopping Center in Ambato. The foundation of this proposal is based on architectural and urban strategies, the result of a thorough analysis of the current conditions of the shopping center. The research, with a qualitative focus, seeks to understand the complexities and potentialities of the facility and its immediate surroundings. In the first instance, theoretical bases are established, both conceptual and strategic, using key strategies extracted from references in similar contexts. Secondly, a detailed survey and analysis of the current market conditions are carried out, proposing diagnostic tables for each element of the facility. This aims to identify both the main potentialities and existing issues. Finally, the previously defined strategies are implemented in the redesign process, marking an approach that preserves the preexisting identity while proposing alternatives for its modernization. The proposal also emphasizes the rescue of identity and respect for what is preexisting as guiding principles to preserve the essence of Mercado Sur while giving it new vitality. Strategic and organized zoning seeks to optimize space usage, creating specific areas for various activities and services. Effective connection between the facility and its immediate public space is highlighted as an essential element. The proposed solutions not only improve the functionality of the market but also transform it into an integral and harmonious component of the urban environment. Therefore, this proposal seeks a significant and sustainable transformation of Mercado Sur and its surroundings, adopting a holistic approach that goes beyond aesthetics, addressing the identified challenges and opportunities comprehensively.